Postsurgical treatment landscape and economic burden of locoregional and distant recurrence in patients with operable nonmetastatic melanoma. Issue 6 (December 2018) - Tarhini, Ahmad; Ghate, Sameer R.; Ionescu-Ittu, Raluca; Manceur, Ameur M.; Ndife, Briana; Jacques, Philippe; Laliberté, François; Nakasato, Antonio; Burne, Rebecca; Duh, Mei Sheng
Abstract : Surgery is the mainstay treatment for operable nonmetastatic melanoma, but recurrences are common and limit patients' survival. This study aimed to describe real-world patterns of treatment and recurrence in patients with melanoma and to quantify healthcare resource utilization (HRU) and costs associated with episodes of locoregional/distant recurrences. Adults with nonmetastatic melanoma who underwent melanoma lymph node surgery were identified from the Truven Health MarketScan database (1 January 2008 to 31 July 2017). Locoregional and distant recurrence(s) were identified on the basis of postsurgery recurrence indicators (i.e. initiation of new melanoma pharmacotherapy, new radiotherapy, or new surgery; secondary malignancy diagnoses). Of 6400 eligible patients, 219 (3.4%) initiated adjuvant therapy within 3 months of surgery, mostly with interferon α-2b ( n =206/219, 94.1%). A total of 1191/6400 (18.6%) patients developed recurrence(s) over a median follow-up of 23.1 months (102/6400, 1.6% distant recurrences). Among the 219 patients initiated on adjuvant therapy, 73 (33.3%) experienced recurrences (distant recurrences: 13/219, 5.9%). The mean total all-cause healthcare cost was $2645 per patient per month (PPPM) during locoregional recurrence episodes and $12 940 PPPM during distant recurrence episodes. In the year after recurrence, HRU was particularly higher in patients with distant recurrence versus recurrence-free matched controls: by 9.2 inpatient admissions, 54.4 inpatient days, 8.8 emergency department admissions, and 185.9 outpatient visits (per 100 person-months), whereas all-cause healthcare costs were higher by $14 953 PPPM. It remains to be determined whether the new generation of adjuvant therapies, such as immune checkpoint inhibitors and targeted agents, will increase the use of adjuvant therapies, and reduce the risk of recurrences and associated HRU/cost. Abstract : Supplemental Digital Content is available in the text.